New Evidence on the Healthy Immigrant Effect - Lídia Farré (Institute for the Study of Labor (IZA), 2013)
This paper provides new empirical evidence on the contribution of selective migration to the health advantage of immigrants upon arrival to the new destination (i.e. the Healthy Immigrant Effect). It analyses a very interesting episode in international migration, namely the exodus of Ecuadorians in the aftermath of the economic collapse in the late 1990s. Between 1999 and 2005, more than 600,000 Ecuadorians left the country and most of them headed towards Spain. Using administrative data from the Vital Statistics, it compares the health distribution (in terms of birth outcomes) of immigrant children born in Spain to that of non-immigrants in Ecuador and immigrants from other nationalities, and not only to that of natives at destination. These comparisons suggest that positive selection is partly responsible for the health advantage of recent immigrants.
Keywords: J61; I14; C14; 330; immigration; selection; health; birth outcomes